Evaluasi Sistem Pendaftaran Online dengan Metode Technology Acceptance Model di Rumah Sakit Umum Daerah K.R.M.T Wongsonegoro Kota Semarang - Finno Harta Dinata; Ida Nurmawati; Indah Muflihatin (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
The online registration system is important component to improve hospital service quality. Regional GeneralHospital K.R.M.T. Wongsonegoro City of Semarang has implemented online registration system since 2017and never been evaluated. An online registration system that is often used by patients is via the MYRSWNapplication, can be downloaded at the play store and app store. Online registration system users in 2019totaling 15,437 users from 199,188 patients. Based on data, it can be seen that users of the online registrationsystem are only 8% of the total number of patients. This shows the user's interest in using the onlineregistration system is very lacking. This research was aimed to analyze the acceptance of an onlineregistration system. The research showed that overview of the online registration system based on aspects ofperceived ease of use can be assessed as easy to learn, quite flexible and easy to use, aspects of perceivedusefulness is considered to have considerable benefits in increasing productivity, making work effective andfast, last aspects of behavioural intention to use tend to be satisfied using the online registration system.Based on aspects of perceived ease of use, perceived usefulness,and behavioural intention to use applicationof an online registration system has been running according to user needs, but it is not free from variousproblems, so there needs a efforts to improvement and development of online registration system through therecommendation of researchers so that online registration system can maintain quality and improve servicequality to patients.